2019
DOI: 10.1093/eurpub/ckz186.344
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ perceptions of difficulties related to frequent users of emergency departments

Abstract: Background Frequent users of emergency department (FUEDs; ≥ 5 ED visits/ year) are often vulnerable individuals cumulating medical, social and substance use problems. FUEDs often require complex and sustained care coordination generally unavailable in ED and are commonly considered contributing to ED crowding. In view of supporting ED health-care providers through specific training and interventions tailored to FUEDs, this study aimed to explore ED healthcare providers’ perceptions of difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This study has several limitations. First, the quantitative survey was not previously validated beyond face validity, although it was used in a previous studies [18,19]. That being said, the survey development went through an expert committee and iterative testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has several limitations. First, the quantitative survey was not previously validated beyond face validity, although it was used in a previous studies [18,19]. That being said, the survey development went through an expert committee and iterative testing.…”
Section: Discussionmentioning
confidence: 99%
“…A 12-item online survey was developed to measure variables related to the FUED issue, summarized below and presented in Appendix 1. The survey was based on a version developed by a panel of experts involved with FUED and used in ongoing research [18,19]. As described in Chastonay et al [19], the panel conducted a series of sessions to develop a set of items exploring ED staff's perceptions regarding FUED and associated issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malone [ 19 ], in her qualitative study, reported that nurses experienced a wide range of difficulties related to the perception of an existing mismatch between the demands of FUEDs and the EDs medico-clinical orientation, resulting in a feeling of failure and affecting their morale. Similarly, a recent pilot qualitative survey in French-speaking Switzerland reported that EDs staff experienced numerous difficulties related to the management of FUEDs suggesting that they may need tailored training, support and resources to address FUEDs’ specific and complex needs [ 20 ]. This has also been addressed in several case reports [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a call from health authorities and hospitals in Switzerland for better care of FUEDs via interventions specifically adapted to them, such as the CM [24]. The importance of the FUEDs issue in Switzerland, as reported in various regional surveys [5,[25][26][27] and the scant information on the perceptions of local ED professionals [20] prompted us to conduct a survey at the national level among ED staff (medical doctors and nurses from different linguistic regions and EDs specialization levels) in order to evaluate: a) the extent to which FUEDs are perceived as an issue; b) their perceived levels of knowledge and understanding of FUEDs; c) levels of perceived usefulness of CM and interest in implementing this intervention in their ED service. Our study focused on the above mentioned aspects within a larger ongoing research project.…”
Section: Introductionmentioning
confidence: 99%